2019
DOI: 10.1017/s1352465819000043
|View full text |Cite
|
Sign up to set email alerts
|

Intrusive social images in individuals with high and low social anxiety: a multi-method analysis

Abstract: Background:Models of social anxiety suggest that intrusive images/memories are common in social anxiety and contribute to the maintenance of social anxiety.Aims:We examined the context and phenomenological features of intrusive social images using quantitative and qualitative measures across various levels of social anxiety.Method:Undergraduate students (n = 191) completed measures of social anxiety (i.e. Social Interaction Anxiety Scale and Social Phobia Scale) and wrote a description of an intrusive social i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…The reports on recurrent experiences of FF imagery are in line with previous research demonstrating the occurrence of negative imagery in social anxiety. The content of FF images in this sample appeared to be similar to that of previously reported negative images in both clinical and non-clinical samples (e.g., descriptions of being judged negatively and performing badly; Hackmann et al, 2000 ; Homer and Deeprose, 2017 ; Ashbaugh et al, 2019 ). Although the present sample could be labeled as an analogue sample, the mean score on the SPS fell above the suggested clinical cut-off score of 24 ( Brown et al, 1997 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The reports on recurrent experiences of FF imagery are in line with previous research demonstrating the occurrence of negative imagery in social anxiety. The content of FF images in this sample appeared to be similar to that of previously reported negative images in both clinical and non-clinical samples (e.g., descriptions of being judged negatively and performing badly; Hackmann et al, 2000 ; Homer and Deeprose, 2017 ; Ashbaugh et al, 2019 ). Although the present sample could be labeled as an analogue sample, the mean score on the SPS fell above the suggested clinical cut-off score of 24 ( Brown et al, 1997 ).…”
Section: Discussionsupporting
confidence: 77%
“…Negative images occur more frequently in individuals with SAD than in individuals without SAD, are rated as more vivid and distressing, and have been found to be more often seen from an observer than from a field perspective (Hackmann et al, 1998;Schreiber and Steil, 2013). In analogue samples of high versus low socially anxious individuals, findings on imagery characteristics have been less consistent (Moscovitch et al, 2011;Ashbaugh et al, 2019). Yet, when instructed to hold a negative versus a neutral image in mind during social interaction or a speech, higher levels of anxiety, more safety behaviors, and worse performance were reported in both SAD groups and non-SAD comparison groups (Hirsch et al, 2003(Hirsch et al, , 2004(Hirsch et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though these results have supported that there are associations between AM content and mental health, numerous studies have not reached such conclusions. Other researchers have observed no significant differences in IAM content as a function of psychopathology, including between dysphoric versus nondysphoric participants 24 and between participants with high versus low social anxiety 25 . Previous work has also failed to find evidence of disorder-congruent content: while AM content from participants with anxiety disorders was significantly different from nonclinical controls, content did not significantly differ across various disorders (i.e., social anxiety disorder versus panic disorder 26 ).…”
Section: Introductionmentioning
confidence: 88%
“…These images are commonly recurrent, spontaneous and from a third-person's perspective (Hackmann et al, 2000). Research has found that, during an anxiety-provoking social task, high social anxiety individuals more commonly experienced negative images and memories (Chiupka et al, 2012) and were more likely to report an observer's perspective (Ashbaugh et al, 2019) compared with low social anxiety individuals. Studies have found that holding an NSI (compared with a neutral selfimage) is associated with an increase in safety-seeking behaviours, anxiety and critical appraisals of social performance (Hirsch et al, 2004;Ng et al, 2014).…”
Section: Social Anxiety Disordermentioning
confidence: 99%